Sharia Fintech Business Analysis at PT. Indonesian Sharia Fund - Huda, M. Ikhwanul (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
The development of technology also has an impact on the development of financial technology, which is currently popular with the term Financial Technology sharia. Sharia fintech is not only owned by banks but there is also a sharia fintech that is independent and has a licence from OJK. One of the Islamic fintechs that is developing in Indonesia in the property sector is dansyariah.id. and this study aims to analyze the contract formula, opportunities and challenges of one of the Islamic Fintechs in Indonesia, namely danasyariah.id. The method used in this research is a literature study that refers to various sources of documents, data and information derived from books, scientific journals, and official websites related to Islamic fintech, especially danasyariah.id to find out the contract formula used in operations, as well as to find out the opportunities and challenges faced by sharia funds.id. the results of this study indicate that danasyariah.id uses murabahah and wakalah bil Ujrah contracts. The challenges faced by Indonesian sharia funds are the lack of public knowledge in sharia fintech, people think that sharia fintech is the same as conventional fintech, limited nominal financing and the amount of capital set by sharia fintech. And among the prospects for Indonesian Sharia Funds are the increasing demand for property, Indonesia's majority Muslim population, capital needs for corporations, entrepreneurs, and MSMEs activists, sharia schemes such as profit sharing are an advantage for Islamic funds, rapid technological developments among the public, and the existence of regulations and legal umbrellas for Islamic fintech from the government. [Abstrak: Semakin berkembangnya tehnologi maka juga berdampak pada perkembangan teknologi keuangan, yang saat ini popular dengan istilah Financial Technology syariah. Fintech syariah tidak hanya dimiliki oleh Perbankan tetapi fintech syariah juga ada yang bersifat independent dan mempunyai Izin dari OJK. Salah satu fintech syariah yang berkembang di Indonesia di bidang property adalah dansyariah.id. dan Penelitian ini bertujuan untuk menganalisis formula akad, peluang dan tantangan salah satu Fintech Syariah di Indonesia yaitu danasyariah.id. Metodologi penelitian yang digunakan dalam penelitian ini adalah studi pustaka yang memanfaatkan berbagai sumber dokumen, data, dan informasi dari buku, jurnal akademik, dan situs resmi fintech syariah, khususnya danasyariah.id. untuk mengetahui formula akad yang dipakai dalam operasional, serta mengetahui peluang dan tantangan yang dihadapi dana syariah.id. hasil penelitian ini menunjukkan bahwa danasyariah.id menggunakan akad murabahah dan wakalah bil Ujrah. Tantangan yang dihadapi oleh dana syariah Indonesia adalah minimnya pengetahuan Masyarakat dalam fintech syariah, masyarakat menganggap bahwa fintech syariah sama dengan fintech konvensional, pembiayaan yang dibatasi Nominalnya dan besarnya modal yang ditetapkan oleh fintech syariah. Dan diantara prospek Dana Syariah Indonesia adalah permintaan dalam property terus meningkat, penduduk Indonesia yang mayoritas Muslim, kebutuhan modal bagi koorporasi, pengusaha, dan pegiat UMKM, skema syariah seperti bagi hasil menjadi keunggulan bagi dana syariah, perkembangan teknologi secara pesat dikalangan Masyarakat, dan adanya regulasi dan payung hukum untuk fintech syariah dari pemerintah.]